Fulminant Hepatic Failure after Chemosaturation with Percutaneous Hepatic Perfusion and Nivolumab in a Patient with Metastatic Uveal Melanoma - Lindsey Teal; Jeffrey Yorio (Case Reports in Oncological Medicine, 2021)
Immune checkpoint inhibitors, such as nivolumab, a programmed death receptor-1 (PD-1) inhibitor, have dramatically improved the treatment of advanced melanomas. Chemosaturation with percutaneous hepatic perfusion (PHP) delivers chemotherapy in high doses directly to the liver and is a potentially effective treatment modality in metastatic uveal melanoma with liver metastases. Its safety and effectiveness have not been studied in patients also receiving immunotherapy. A 46-year-old male with a history of uveal melanoma of the right eye was found to have liver metastases. He was treated with PHP using high-dose melphalan for 6 months with a partial response followed by progression. Two months after his last PHP treatment, the patient was started on nivolumab. After two doses of nivolumab, the patient developed severe hepatitis that progressed to fulminant hepatic failure and death despite treatment with high-dose corticosteroids and mycophenolate mofetil. Nivolumab and other immune checkpoint inhibitors have been effective in treating advanced melanoma and extending life. However, there are serious immune adverse events that can occur. While hepatitis after taking nivolumab has been documented, fulminant hepatic failure is rare. We believe that prior PHP treatment contributed to the severity of the hepatitis and, ultimately, fulminant hepatic failure. To our knowledge, this is the only case of fulminant hepatic failure secondary to a checkpoint inhibitor with preceding PHP. Specific precautions should be made in patients who have been exposed to PHP in the past, and further studies should be done to assess the safety of using checkpoint inhibitors after PHP.